Novel Mutation of Tyrosinemia in a Child With Hypophosphatemic Rickets. Issue 2 (25th May 2022) - Dogra, Surabhi; Kumar, Karunesh; Malik, Rohan; Malhotra, Smita; Sibal, Anupam
Abstract : Tyrosinemia is an inherited metabolic disease of fumarylacetoacetate enzyme. A male infant presented to us with clinical features of rickets, floppiness, and a deranged coagulation profile. A novel mutation causing Tyrosinemia was discovered on the basis of genetic sequencing.